PEMBUATAN BRIKET ARANG DENGAN MEMANFAATKAN LIMBAH DARI TEMPURUNG BIJI KETAPANG (Terminalia catappa) DAN TEMPURUNG BIJI KEMIRI (Aleurites molucanna L. Willd.) - Sandi Christopher Hutagalung; Erwin Erwin; Aman Sentosa Panggabean (PROSIDING SEMINAR KIMIA, 2017)
Tropical almond (Terminalia catappa) seed shell and candlenut (Aleurites molucanna L. Willd) seed shell has a huge potential as a source of alternative energy in the manufacture of coal briquettes. This research has been conducted using method of carbonization, mixing, molding, drying and then the briquettes quality was analyzed with test parameters namely inherent moisture content, ash content, volatile matter content, fixed carbon content and calorific value. The results showed that mixture of tropical almond seed shell and candlenut seed shell can be used as briquettes. In this study, the best quality briquettes with mixture variation of tropical almond seed shell and candlenut seed shell was obtained in mixture variation of 25% tropical almond seed shell and 75% candlenut seed shell with calorific value was 5043 cal/gr, fixed carbon content was 47.22%, volatile matter content was 25.96%, ash content was 4.7% and inherent moisture content was 22.11%. But 100% candlenut seed shell also have a good quality briquettes with calorific value was 5098 cal/gr, fixed carbon content was 47.23%, volatile matter content was 28.44%, ash content was 4.24% and inherent moisture content was 20.08%. Keywords: Briquette, Carbonization, Calorific Value, Terminalia catappa, Aleurites molucanna L. Willd